2016
DOI: 10.1186/s12889-016-3033-x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and linkage into care over one year of providing HIV testing and counselling through community and health facility testing modalities in urban informal settlement of Kibera, Nairobi Kenya

Abstract: BackgroundWe examine the uptake of HIV Testing and Counselling (HTC) and linkage into care over one year of providing HTC through community and health facility testing modalities among people living in Kibera informal urban settlement in Nairobi Kenya.MethodsWe analyzed program data on health facility-based HIV testing and counselling and community- based testing and counselling approaches for the period starting October 2013 to September 2014. Univariate and bivariate analysis methods were used to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
6
0
1
Order By: Relevance
“…In order to contribute to the global efforts for ending AIDS, we designed and implemented a strategy for universal HIV testing and enrolment to care of all infected children/adolescents in RLS. Our model of multiple entry points to healthcare was highly accepted by parents/legal guardians (> 99%), similar to findings from Uganda (92.8%) and Kenya (82.5%) [ 11 , 13 , 14 ]. These indicate a high success rate of such approach in RLS, which contributes in achieving the 90% HIV diagnosis among children/adolescents with unknown status [ 9 ].…”
Section: Discussionsupporting
confidence: 82%
“…In order to contribute to the global efforts for ending AIDS, we designed and implemented a strategy for universal HIV testing and enrolment to care of all infected children/adolescents in RLS. Our model of multiple entry points to healthcare was highly accepted by parents/legal guardians (> 99%), similar to findings from Uganda (92.8%) and Kenya (82.5%) [ 11 , 13 , 14 ]. These indicate a high success rate of such approach in RLS, which contributes in achieving the 90% HIV diagnosis among children/adolescents with unknown status [ 9 ].…”
Section: Discussionsupporting
confidence: 82%
“…A number of studies on HIV testing and linkage to care in other SSA countries have reported linkage rates of more than 60%. 15 21 26–29 Our encouraging findings likely reflect a combination of health system and social changes, including reduction in stigma. Our study itself may also have increased linkage to care through regularly contacting and following up HIV-positive individuals.…”
Section: Discussionmentioning
confidence: 69%
“…In urban and mixed urban and rural communities in which both facility- and community-based HTC strategies can be implemented, however, limited data has been available to inform the prioritization of finite HTC resources for the general population. Although many studies have evaluated comprehensive door-to-door HBHTC in sub-Saharan Africa, we found only one that did so in combination with PITC in urban settings [8]. In Nairobi, Kenya, Muhula and colleagues compared facility-based PITC and client initiated testing with CBHTC; however, the relative contribution of testing strategies to new diagnoses identified and associated costs were not reported [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have evaluated comprehensive door-to-door HBHTC in sub-Saharan Africa, we found only one that did so in combination with PITC in urban settings [8]. In Nairobi, Kenya, Muhula and colleagues compared facility-based PITC and client initiated testing with CBHTC; however, the relative contribution of testing strategies to new diagnoses identified and associated costs were not reported [8].…”
Section: Discussionmentioning
confidence: 99%